The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00421-011-2203-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-peroxidation and peroxiredoxin-overoxidation in the erythrocytes of non-insulin-dependent type 2 diabetic men during acute exercise

Abstract: Single bouts of exercise induce an acute state of oxidative stress. It is largely unknown what this means in the context of diseases which are associated with increased oxidative stress, e.g., type 2 diabetes mellitus (T2DM). Free radicals can destroy the structure of erythrocytes and reduce their deformability. Antioxidative peroxiredoxins are highly abundant in erythrocytes. Therefore, we immunohistochemically examined whether the free radical-induced erythrocyte lipid-peroxidation measured by 8-iso-prostagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In line with these ideas, PRDX6 levels were significantly higher in diabetic patients with endothelial dysfunction compared with control subjects, which may possibly represent a physiological adaptation against oxidative stress in patients with atherosclerosis (44). Moreover, another study (45) conducted in diabetic patients demonstrated that physical training was able to increase PRDXs levels measured in erythrocytes, counteracting the oxidative damage that is typical of diabetes. These results are important in outlining the role of the PRDX family in the management of glucose homeostasis and in the prevention of diabetes and cardiovascular disease in diabetic patients, likely reducing the inflammatory state and oxidative stress.…”
Section: Discussionmentioning
confidence: 57%
“…In line with these ideas, PRDX6 levels were significantly higher in diabetic patients with endothelial dysfunction compared with control subjects, which may possibly represent a physiological adaptation against oxidative stress in patients with atherosclerosis (44). Moreover, another study (45) conducted in diabetic patients demonstrated that physical training was able to increase PRDXs levels measured in erythrocytes, counteracting the oxidative damage that is typical of diabetes. These results are important in outlining the role of the PRDX family in the management of glucose homeostasis and in the prevention of diabetes and cardiovascular disease in diabetic patients, likely reducing the inflammatory state and oxidative stress.…”
Section: Discussionmentioning
confidence: 57%
“…The precise interaction between these two interventions remains to be established, as exercise training seems to provide no additional benefit when used in combination with caloric restriction [100]. Although individuals with T2D show elevated oxidative stress after maximal-intensity exercise compared to healthy individuals, 12 weeks of preconditioning with regular aerobic training markedly diminished oxidative stress in response to an acute bout of exercise in individuals with T2D [101]. …”
Section: Effects Of Acute and Chronic Exercise On Oxidative Stress Inmentioning
confidence: 99%
“…Increased levels of oxidised PRDX (I–IV) dimers [86] and over-oxidised monomers [70] , [87] , [88] have been reported in immune cells and erythrocytes following exercise. Under cellular oxidative stress, the PRDX decamer can expose an oxidised cysteine that resolves with a neighbouring PRDX thiol to form a stable oxidised dimer.…”
Section: Is Prdx a Peroxide Sensing Protein During And Following Exermentioning
confidence: 99%
“…This ‘over-oxidation’ occurs at a rate too quickly for thiol ‘resolution’ and leads to the formation of over-oxidised monomers. Over-oxidised PRDX monomers have been reported during and following exercise in human peripheral blood mononuclear cells (PBMCs) [93] , [87] and erythrocytes respectively [88] . Formation of over-oxidised PRDX in PBMCs (I–IV isoforms) has been shown to be dependent on the intensity of exercise, with heightened peroxide concentrations during high intensity exercise (80% maximal oxygen consumption [ O 2max ] vs. 60% O 2max ) likely exceeding the reduction power of TRX, the exclusive reductant of the PRDX (I–IV) disulphide [93] .…”
Section: Is Prdx a Peroxide Sensing Protein During And Following Exermentioning
confidence: 99%